Analisis determinan kemiskinan dan hubungannya dengan program pengentasannya Kabupaten/Kota di Provinsi Jambi - Henny Nurafni; M. Rachmad. R; Muhammad Safri (Jurnal Paradigma Ekonomika, 2021)
This study aims to analyze the level of welfare of rice farmers in the Air Hangat Timur District and determine the factors that influence it. Welfare, in this case, is measured by using income. The number of samples as many as 98 farmers from the size of the population of rice farmers in the East Air Warms sub-district of 3531 rice farmers. Multiple regression model analyzed data. The study results found that rice farmers in Air Warm Timur District were relatively prosperous with a per capita income of IDR 5,053,227 per year. The size of the farmer's income is influenced by the number of dependents, yields, and capital.